Utilization of banana peel as funtional ingredient in product development - Mohd Dom, Zanariah; Azhar, Adibah Zahiah; Masaudin, Saidatul Nurul Atika (HH Publisher, 2022)
The agro-food industry’s exponential growth of plant waste production is a critical global issue, taking into account its storage, disposal, environmental impact and potential health risks. However, by-product utilisation of agricultural waste for the retrieval of addedvalue compounds offers new avenues for industrial production and waste management. Bananas waste primarily the peels are potentially a useful source for the substitution of value added products such as dietary fibres, bioactive components, including carotenoids, polyphenols, pro-vitamins as well as essential minerals. This project describes the types and the composition of raw banana peel wastes and the bioactive components of the peel, the processing methods and the possible application of banana peel flour (BPF). Of particular interest, the proximate analysis and physicochemical properties of potential BPF and the properties of the by-product are discussed. This information was then used to identify types of food that is suitable for the production industry. Then, the utilisation of banana peel flour in waffle ice cream cones and yellow noodles were chosen. The formulations of BPF were prepared in three different formulations: 10%, 20% and 30% for banana peel noodles and 5%, 10% and 20% for waffle cones, respectively. Overall, BPF substitutions in these food products have affected and improved the cooking properties, nutritional values, colour, texture and sensory characteristics compared to control without any substitution.